(untitled) (Communications in Computational Physics, 2020)
Numerical methods based on gyrocenter gauge kinetic theory are suitable for first principle simulations of high frequency waves in magnetized plasmas. The δf gyrocenter gauge PIC simulation for linear rf wave has been previously realized. In this paper we further develop a full-f nonlinear PIC algorithm appropriate for the nonlinear physics of high frequency waves in magnetized plasmas. Numerical cases of linear rf waves are calculated as a benchmark for the nonlinear GyroGauge code, meanwhile, nonlinear rf-wave phenomena are studied. The technique and advantage of the reduction of the numerical noise in this full-f gyrocenter gauge PIC algorithm are also discussed.